2019
DOI: 10.1177/1176934319853580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Gene Expression of Glutathione Peroxidase 1 in Tor tambroides Exposed to Temperature Stress

Abstract: Temperature is an abiotic factor that affects various biological and physiological processes in fish. Temperature stress is known to increase the production of reactive oxygen species (ROS) that subsequently cause oxidative stress. Fish is known to evolve a system of antioxidant enzymes to reduce ROS toxicology. Glutathione peroxidase (GPx) family consists of key enzymes that protect fish from oxidative stress. In this study, full-length GPx1 cDNA (GenBank accession no. KY984468) of Tor tambroides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…However, fish are known to have developed an antioxidant enzyme system to reduce ROS. Among these enzymes, GPx is a key protein that protects fish from oxidative stress [26]. Our data support this idea, as we detected significantly increased levels of GPx activity at 12 h post-hypoxia stress.…”
Section: Discussionsupporting
confidence: 87%
“…However, fish are known to have developed an antioxidant enzyme system to reduce ROS. Among these enzymes, GPx is a key protein that protects fish from oxidative stress [26]. Our data support this idea, as we detected significantly increased levels of GPx activity at 12 h post-hypoxia stress.…”
Section: Discussionsupporting
confidence: 87%
“…In that regard, it is interesting to note that also the gene regulation response registered by our work seems to be dependent on the Se/ Hg molar ratio of the feed and not on the Hg concentration alone. However, it must also be borne in mind that the response may be different depending on the stressor: cold temperature stress, for example, induced a downregulation of gpx1 redox genes in the cyprinid Tor tambroides [36], but infection with a pathogen induced the expression at the transcriptional level of both txn and txnrd in rainbow trout [15]. The upregulation in the transcription of the genes txn1, gpx1, and txnrd2 observed in A2 relative to A1 parallels a higher DNTB-reductase activity in these groups, while the increase in TrxR activity in A2 mirrors the upregulation of txn1 and txnrd2.…”
Section: Phase Amentioning
confidence: 99%
“…The present results showed that water temperature above 30 • C induces oxidative stress in D. labrax accompanied by ROS production. This finding is supported by the research conducted by Kamyab et al (2017) and Do et al (2019). Biller and Takahashi (2018) reported that oxidative stress limits the immune response by impairing the defense mechanism associated with ROS production to decrease ROS production.…”
Section: Discussionmentioning
confidence: 52%